Pendidikan Nilai sebagai Fondasi Pembentuk Karakter Siswa di Era Digital - Purba, Araida; Ndona, Yakobus; Saragi, Daulat (SENTRI: Jurnal Riset Ilmiah, 2025)
This study explores the role of value education as the foundation for character formation among students in the digital era. The ongoing digital transformation has brought significant impacts on the educational process, particularly in shaping students’ character. The rapid advancement of technology presents new challenges, including the risk of gadget addiction, the spread of negative information, and the decline of moral values, all of which must be addressed through systematic value education. This article discusses the function of value education as a fundamental element in character building within the digital age by employing a conceptual approach and literature review from various recent studies. The findings reveal that the integration of value education into the curriculum and the learning environment is essential to develop students who are adaptive, responsible, and ethical in facing the dynamic nature of digital life. Furthermore, the study emphasizes that adaptive strategies, innovative pedagogy, and the ethical use of digital technology are crucial to strengthening students’ character development. Value education not only acts as a medium for transferring moral principles but also as a guide for students to apply these values in real-life digital interactions. Ultimately, this research concludes that value education serves as a vital pillar in preparing a generation grounded in moral integrity and social responsibility amidst the rapid technological changes of the modern world.